Guided reading and literacy workstation towards reading motivation - Abdullah Sani, Atiqah; M. Anthony, Elizabeth (Penerbit UTHM, 2020)
Research has widely documented that reading achievement is the most influential determinant of a child's educational success; yet, large gaps still remain for many children (e.g., Butler, Marsh, Sheppard, & Sheppard, 1985; Senechal & LeFevre, 2002; Stainthorp & Hughes, 2004; Wagner el al, 1997). As Asraf and Ahmad (2003) point out, the rural school students' failure rate in national standardized English examination is twice that of the students from urban area..